2007
DOI: 10.2754/avb200776030391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long and Short-Term Progestagen Treatments Combined with PMSG on Oestrus Synchronization and Fertility in Awassi Ewes during the Breeding Season

Abstract: Synchronization of oestrus has been used to increase reproductive effi ciency in most animals, including ewes. The aim of the present study was to compare the effect of the length of a progestagen treatment (12 d vs. 6 d) on synchronization effi ciency (oestrus response, time to onset of oestrus and duration of oestrus) and fertility rate using fl uorogestone acetate (FGA) progestagen sponge treatment with pregnant mare serum gonadotropin (PMSG) administration applied at different times of sponge removal. Ewes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
36
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 20 publications
15
36
4
3
Order By: Relevance
“…The low pregnancy rate in this study might also be attributed to semen cryopreservation, as the sperm cell motility used for AI was B40% post-thaw. Pregnancy rate of 34.3% for the long-term progestagen treated does was also lower compared to the pregnancy rate of 46.7% reported by Motlomelo (Vinoles et al 2001;Greyling et al 2002;Ustuner et al 2007;Tibary 2009). Three does in this trial did not show any signs of oestrus following treatment (two unimproved indigenous goats and one Boer goat).…”
Section: Resultscontrasting
confidence: 52%
“…The low pregnancy rate in this study might also be attributed to semen cryopreservation, as the sperm cell motility used for AI was B40% post-thaw. Pregnancy rate of 34.3% for the long-term progestagen treated does was also lower compared to the pregnancy rate of 46.7% reported by Motlomelo (Vinoles et al 2001;Greyling et al 2002;Ustuner et al 2007;Tibary 2009). Three does in this trial did not show any signs of oestrus following treatment (two unimproved indigenous goats and one Boer goat).…”
Section: Resultscontrasting
confidence: 52%
“…The growth rate of follicle per day was 0.50 mm in group I and 0.90 mm in group II ( Ustuner et al, (2007) who also reported estrus response of 100 per cent, using progesterone intravaginal sponges and PMSG treatment. Thus the addition of PMSG induced estrum in all the does in group II and group III, irrespective or the dose levels used.…”
Section: Resultsmentioning
confidence: 89%
“…Ovulatory response was rather fast, maybe due to the administration of 750 IU/ewe. eCG has been shown to reduce the interval between sponge withdrawal and estrus and improve the efficiency of synchronization of estrus and ovulation during the breeding season [38]. However, fertility rate tends to be maximum when AI is performed at the second half of the estrous, a few hours before ovulation [39].…”
Section: Ovarian Response To Short-term Progestagen Treatmentsmentioning
confidence: 99%